Multidrug resistant Aeromonas infection following medical leech therapy: A case report and development of a joint antimicrobial stewardship and infection prevention protocol. (December 2020) - Masters, Mary Clare; Gupta, Aakash R.; Rhodes, Nathaniel J.; Flaherty, John P.; Zembower, Teresa R.; Alghoul, Mohammed; Krueger, Karen M.
Highlights: Aeromonas sp. infections are a recognized complication of medical leech therapy. Antimicrobial prophylaxis is typically used for patients having medical leech therapy. We describe a leech-related infection resistant to all first line prophylactic agents. In response, we developed an antimicrobial stewardship-infection prevention protocol. Abstract: Objective: Aeromonas sp. infections are a recognized complication of medical leech therapy (MLT). In patients requiring MLT, ciprofloxacin or trimethoprim–sulphamethoxazole are commonly used to prevent such nosocomial infections. After a patient at our institution developed a MLT-associated multi-drug resistant (MDR) Aeromonas infection, we developed and evaluated a joint antimicrobial stewardship and infection prevention protocol for MLT at our institution. Methods: We describe a case of a surgical site infection with MDR Aeromonas following MLT that was resistant to typically prescribed prophylactic antimicrobials, and development of a new leech culture protocol to proactively monitor for antimicrobial resistance among our institution's leech supply. We also report the rates of MLT-associated infections prior to and following implementation of this protocol and the antimicrobial susceptibility profiles detected in leech culture at our institution. Results: Between October 2014 and February 2018, 46 patients received MLT at our institution. Other than the case described in this report, no other instances of MLT-related infections were noted during this time period. Culture results from 22 leeches in six batches since February 2018 showed that all were susceptible to ciprofloxacin, TMP-SMX, and ceftriaxone. Since initiation of a leech culture protocol, no further cases of MLT-associated infections have been reported at our institution. Conclusions: In light of increasing antimicrobial resistance and the potentially devastating consequences of MLT-associated infections, institutions offering MLT should be aware of these risks and ensure that protocols are in place to minimize infection risks for patients.